Classic Edition Sources: Anthropology - Angeloni Elvio (Mc Graw-Hill, 2007)
This reader provides over 40 selections of enduring intellectual value--classic articles, book excerpts, and research studies--that have shaped the study of anthropology and our contemporary understanding of it.